Spatial variability of physical, chemical, and biological properties of agricultural soils in Hidalgo State, Mexico : Agricultural soil properties (Agro Productividad, 2021)
Objective: To establish the influence on soil fertility by spatial variations of physical, chemical, and biological properties of two agricultural soils in the state of Hidalgo (Mexico).Methodology: Soils A, (clay-sandy, shallow horizon imperfect drainage), the municipality of Apan and soil B (with a light phase and thick, with stones), the municipality of Emiliano Zapata, were sampled in a network of 10x10m at 10, 20 and 40 cm Deep. Four plots that have been under a malting barley monoculture system for more than 40 years were sampled. Physical, chemical and biological parameters were determined, following the official Mexican standard for soils.Results: The C/N ratio of both soils had a low spatial variation due to its relationship with stable fractions of soil organic matter (humus) and relatively low content. The spatial variability increased significantly with depth in both soils, while the apparent density showed little spatial variation. In addition, random behavior was observed at short distances (for available phosphorus, enzymatic activity and nitrates). The spatial variability of interaction between exchangeable bases, K / (Ca + Mg) was greater than that of each element individually. The results showed that the concentrations of nutrients and the biological processes that affect their availability in the soil did not have a uniform spatial distribution, so that the applications in the fertilizer of the cultivated soil must adapt to these variations (site-specific fertilization).Conclusions: There is a significant spatial of the soils dedicated for more than 40 years to the monoculture of malting barley. Nutrients and biological processes see their availability in soils affected. It is understood that applications of fertilizers to the soil are required to overcome and adapt to these variations (site-specific fertilization).